Does Education Affect Rural Women’s Trust? Evidence From China - Xu, Siyu; Zhao, Yeye; Aziz, Noshaba; He, Jun (Frontiers in Psychology, 2022)
Trust is of great significance to the economic and social development of a country. In the case of China, the trust of rural women has undergone tremendous changes along with the development of rural areas. It is seen that the trust of rural women has changed from localized to generalized trust, and it is stated that the major factor leading to this transformation is education. To explore the phenomenon empirically, the current study uses the survey data of rural women sourced from China Family Panel Studies (CFPS) over the year 2018. Through the ordered probit model, the study reveals that education plays a significant role in influencing rural women’s generalized trust and localized trust. Through mediation analysis, the study further reveals that reliance on Internet information, access to public resources, and income are the factors mediating the relationship between education and generalized trust. Besides, the outcomes further unveil that the impact of education on localized trust is stronger when the level of mobility is low. For robustness check, the current study additionally employs a regression discontinuity model. The overall findings elucidate that education is the major factor triggering the trust of rural women in China. The findings propose that policymakers in China should imply education-oriented strategies as individuals with higher levels of education are more inclined to trust others.